Přístupový systém pro aplikaci carsharing - Texl, Filip (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2023)
Bakalářská práce se věnuje přístupovým systémům s důrazem na carsharingové aplikace, a to jak z teoretického hlediska, kdy analyzuje jejich výhody, nevýhody a použitá kryptografické primitiva, tak i z hlediska praktického, kdy v praktické části je návrh přístupového systému a jeho následná realizace. V bakalářské práci se též využívá technologie Bluetooth Low Energy a Near Field Communication, které jsou opět popsány z teoretického hlediska, zejména pak klíčové pojmy těchto technologií, tak i jejich praktické využití pro přístupové systémy.

The bachelor thesis is devoted to access systems with an emphasis on carsharing applications, both from a theoretical point of view, where it analyzes their advantages and disadvantages and uses cryptographic primitives, and also from a practical point of view, where the practical part includes the design of an access system and its subsequent implementation. Bluetooth Low Energy technology and Near field communication are also used in the bachelor thesis, which is again described from a theoretical point of view, especially the key concepts of these technologies, as well as its practical use for access systems.
Access control system for carsharing application
Keywords: Advanced Encryption Standard; autentizace; Bluetooth; Bluetooth Low Energy; Java; Kotlin; Near field communication; NFC čtečka; přístupové systémy; sokety; symetrická kryptografie; TCP komunikace; Access control systems; Advanced Encryption Standard; authentication; Bluetooth; Bluetooth Low Energy; Java; Kotlin; Near field communication; NFC reader; sockets; symetric cryptography; TCP communication